Local Wisdom: Tourism Object Owner's Strategy during the Covid-19 Pandemic in Karo Land - Lukita Ningsih; Azizul Kholis (Budapest International Research and Critics University, 2021)
The impact of the COVID-19 outbreak on the managers or owners of tourism objects in Karo land has an impact on all aspects of the community's economic life, one of the sectors most affected by the global pandemic in the tourism service sector. Almost all areas in North Sumatra that develop the tourism sector have experienced a decline in income and the closure of all access roads leading to tourist attractions. One of the tourism areas that have felt the impact of the pandemic is Tanah Karo. The essence presented in this article is how local wisdom can be used and developed as a strategy by the owner of tourism objects in Tanah Karo for the sustainability of his business in the tourism sector by utilizing technological sophistication, namely by promoting the marketing of tourism products based on local wisdom through online media. This type of qualitative research is used with a descriptive approach. Data is collected by interviewing the owner or manager of a tourist attraction, the government and workers in the tourism sector, document review, and observation of the location of a tourist attraction. The strategy of the owner of a tourism object business for business sustainability in the Karo land tourism sector by utilizing local wisdom of the Karo land community in the form of natural beauty, cultural customs, arts, agricultural products in the form of flower plants, picking their own fruit, which are packaged in an attractive and promoted manner market by utilizing digital technology in virtual and other forms. Local wisdom developed by business owners of tourism objects in Karo lands also has an economic impact on tourism sector workers, local communities, thereby reducing unemployment caused by the closure of tourist attractions in Karo lands.